Event Management in Sport, Recreation and Tourism: Theoretical and Practical Dimensions - Cheryl Mallen; Lorne James Adams (New York Routledge, 2017)
Now in a fully revised and updated third edition, Event Management in Sport, Recreation and Tourism provides a comprehensive theoretical and practical framework for planning and managing events. Focusing on the role of event managers and their diverse responsibilities through each phase of the event planning process, this is still the only textbook to define the concept of knowledge in the context of event management, placing it at the centre of professional practice.
Keywords: Sports; Management; Recreation; Tourism; (ETB-2003) Conference and Events Management